Aeromonas Hydrophilia as a Rare Cause of Septic Arthritis in a Hemodialysis Patient - Rosli, Saarah Huurieyah Wan; Ding, Chuan Hun; Wahab, Asrul Abdul (Journal of Medicine, 2020)
Septic arthritis usually represents a direct invasion of joint space by various microorganisms, most commonly caused by bacteria. Most of the time, it is caused by Staphylococci spp. or Streptococci spp. This is a case of a 70-year-old Chinese man with underlying end stage renal failure on regular hemodialysis who presented with recurrent right shoulder pain and swelling. He was diagnosed with right shoulder septic arthritis whereby arthrotomy was performed. Intra-operative tissue specimen from his right shoulder grew Aeromonas hydrophilia which was susceptible to ceftriaxone, cefepime, ciprofloxacin, gentamicin and sulfamethoxazole-trimethoprim. He was given intravenous cefepime for 21 days and discharged after treatment completed. J MEDICINE JUL 2020; 21 (2) : 113-116